Acessibilidade informacional no contexto da mediação da informação em bibliotecas universitárias: um estudo de caso na Biblioteca Setorial do Centro de Ensino Superior do Seridó - CERES/UFRN - Santos, Francimária Lucena dos (2019)
This research aims to evaluate the accessibility of the physical and informational structure in the Sector Library of the Seridó Higher Education Center of the Federal University of Rio Grande do Norte - CERES, in the city of Caicó / RN, for users with disabilities and specific educational needs. It aims to understand information accessibility in the context of information in university libraries, diagnose the information accessibility resources present in the university library for users with special educational needs, both in relation to the physical space and the resources and services available to this public, as well as check with the librarians, which actions and strategies of information mediation for users with special needs are being performed and which may be performed in this context. For this, a case study was conducted from an unstructured interview with the librarian responsible for the library, which proved the existence of information mediation for users with disabilities. However, it was found that the possibilities are very low due to the barriers encountered by the lack of resources available in the unit to serve the community of users with specific educational needs.